Using high-performance cementitious mortar and external prestressing for retrofitting of corroded reinforced concrete beams. Issue 15 (November 2020) - Atta, Ahmed; Taman, Mohamed
The effect of using high-performance polypropylene fiber–reinforced cementitious mortar on reinforced concrete beam repair was presented in this article. Results of an experimental study for the flexural performance of 13 reinforced concrete beams were presented. The corrosion level, in terms of the mass loss of steel, was estimated to be 10% and 15%. Three non-strengthened specimens were tested as a reference: one control uncorroded specimen and two control specimens corroded with 10% and 15%. Ten specimens were strengthened using different techniques; replacement of the spilled concrete at the tension zone with 40-mm-thick high-performance polypropylene fiber–reinforced cementitious mortar, using external prestressing bars at the tension zone with adding 20-mm-thick high-performance polypropylene fiber–reinforced cementitious mortar at the compression zone, and a combination of these techniques. The prestressing reinforcing bars stress was chosen to be 0.25 fpy and 0.38 fpy for the corroded 10% specimens and 0.25 fpy for the corroded 15% specimens. A combination of 40-mm-thick high-performance polypropylene fiber–reinforced cementitious mortar at the tension side and external prestressing bars at the tension zone increased the specimen capacity by 15% and 34% compared with the uncorroded and 10% corroded control specimens, respectively. A comparative study was conducted to evaluate the efficiency of various strengthening techniques. An analytical model was proposed in order to give design guidelines.